Acupuncture for somatosensory deficits after stroke: a systematic review and meta-analysis - Ren, Shumeng; Chen, Yuhang; Liu, Yu; Lv, Qiuyi; Peng, Jing; Song, Lei; Zou, Yihuai; Zhang, Hua; Chen, Xing (Frontiers in Medicine, 2025)
ObjectiveThis meta-analysis aimed to evaluate the randomized controlled trials (RCTs) of acupuncture for somatosensory deficits after stroke to provide the current best evidence for clinical practice.MethodsA systematic search was performed for eligible articles on the acupuncture for somatosensory deficits after stroke based on 14 databases. Two reviewers independently screened the RCTs, extracted data, and evaluated the methodological quality. A meta-analysis of RCTs was conducted using STATA 11.0 software.ResultsA total of 57 RCTs were included. Meta-analysis results showed that compared with the control group, the acupuncture group had a higher effective rate [risk ratio (RR) = 1.21, 95% CI (1.17, 1.24), I2 = 10.6%, P < 0.001] and a better sensory disturbance score [mean difference (MD) = 5.37, 95%CI (3.81, 6.92), I2 = 93.9%, P < 0.001]. The Visual Analog Scale in the acupuncture group was lower [MD = −1.44, 95%CI (−1.81, −1.07), I2 = 94.5%, P < 0.001]. The acupuncture also showed an improvement in the ability of daily living [MD = 12.19, 95% CI (8.50, 15.87), I2 = 97.2%, P < 0.001] and the symptoms of neurological deficit [Standardized Mean Difference (SMD) = −1.53, 95%CI (−2.04, −1.03), I2 = 89.7%, P < 0.001].ConclusionsThe current best evidence shows that acupuncture has advantages in raising the effective rate, alleviating sensory disturbance, relieving pain, enhancing the ability of daily living, and improving the symptoms of neurological deficits for somatosensory deficits after stroke compared with the control group. And the adverse reactions in acupuncture group were acceptable. However, further well-designed high-quality and multicenter international studies are needed to verify the effectiveness and safety of acupuncture for somatosensory deficits after stroke.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020186040.